HCV modifies EGF signalling and upregulates production of CXCR2 ligands: Role in inflammation and antiviral immune response - Gröpper, Christina; Bartenschlager, Ralf (Journal of hepatology, 2018)
Background & Aims - To affect immune response and inflammation, the hepatitis C virus (HCV) substantially influences intercellular communication pathways that are decisive for immune cell recruitment. The present study investigates mechanisms by which HCV modulates chemokine-mediated intercellular communication from infected cells. - Methods - Chemokine expression was studied in HCVcc-infected cell lines or cell lines harbouring a subgenomic replicon, as well as in serum samples from patients. Expression or activity of mediators and signalling intermediates was manipulated using knockdown approaches or specific inhibitors. - Results - HCV enhances expression of CXCR2 ligands in its host cell via the induction of epidermal growth factor (EGF) production. Knockdown of EGF or of the p65 subunit of the NF-κB complex results in a substantial downregulation of HCV-induced CXCR2 ligand expression, supporting the involvement of an EGF-dependent mechanism as well as activation of NF-κB. Furthermore, HCV upregulates expression of CXCR2 ligands in response to EGF stimulation via downregulation of the T-cell protein tyrosine phosphatase (TC-PTP [PTPN2]), activation of NF-κB, and enhancement of EGF-inducible signal transduction via MEK1 (MAP2K1). This results in the production of a cytokine/chemokine pattern by the HCV-infected cell that can recruit neutrophils but not monocytes. - Conclusions - These data reveal a novel EGF-dependent mechanism by which HCV influences chemokine-mediated intercellular communication. We propose that this mechanism contributes to modulation of the HCV-induced inflammation and the antiviral immune response. - Lay summary - In most cases hepatitis C virus (HCV) results in chronic infection and persistent viral replication, taking decades until development of overt disease. To achieve such a course, the respective virus must have developed mechanisms to circumvent antiviral response, to modulate the inflammatory response and to utilise the infrastructure of its host with moderate effect on its viability. The present study provides novel data indicating that HCV induces epidermal growth factor production in its host cell, enhancing epidermal growth factor-inducible expression of chemokines that bind to the CXCR2 receptor and recruit neutrophile granulocytes. Importantly, chemokines are critical mediators determining the pattern of immune cells recruited to the site of injury and thereby the local inflammatory and immunological milieu. These data strongly suggest that HCV triggers mechanisms that enable the virus to influence the inflammatory and immunological processes of its host.
Gesehen am 17.05.2019